2010
DOI: 10.1080/1331677x.2010.11517423
|View full text |Cite
|
Sign up to set email alerts
|

Financing Gap for SMES and the Mezzanine Capital

Abstract: Mezzanine capital is a hybrid instrument which combines the benefits of debt and equity

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 2 publications
1
22
0
2
Order By: Relevance
“…While we could not in absolute evaluate either the supply of or demand for such funds, due to issues discussed by Vasilescu (2010), our analyses have shown significant 'pressures' on the demand side, which were not followed by proportional increases or adjustments on the supply side, leading to the widening of the mismatch (gap). In terms of hypothesis 2, the results of our power analyses and the corresponding effect sizes have clearly shown that large companies were able to secure higher levels of additional financing, decreasing inventories and adjusting their net working capital.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…While we could not in absolute evaluate either the supply of or demand for such funds, due to issues discussed by Vasilescu (2010), our analyses have shown significant 'pressures' on the demand side, which were not followed by proportional increases or adjustments on the supply side, leading to the widening of the mismatch (gap). In terms of hypothesis 2, the results of our power analyses and the corresponding effect sizes have clearly shown that large companies were able to secure higher levels of additional financing, decreasing inventories and adjusting their net working capital.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, we used a novel power analysis methodological approach. Complementing and extending the work by Vasilescu (2010) on the SME financing gap publish recently in Ekonomska istraživanja we have employed a differential approach, and further estimated the effect size changes in company capital structures in Slovenia.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability of SMEs to grow depends highly on their potential to invest in restructuring, innovation and qualification. But all of these investments need capital and therefore access to finance (Giurca Vasilescu, 2010).…”
Section: Financing Innovation In Smementioning
confidence: 99%